The role of social influence model in social media marketing / Saiful Bahri Mohd Kamal... [et al.] - Mohd Kamal, Saiful Bahri; Zainol, Noorliza; Mahat, Fadhlina; Abdullah, Dahlan; Bahari, Khairil Anuar; Azmi, Nuruddin (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Over the past few years, hotel businesses have acknowledged the huge role of social media in facilitating and assisting business growth due to its ease-of-use and speed of reach in nature, which essentially allow businesses to perform a role in social media marketing, where businesses can personally engage in advertising and promotion-related activities towards online customers. Nevertheless, hotel businesses are unable to effectively exploit social media marketing as they have a restricted knowledge on how to get potential customers to actively engage and become proactive as well as influence customers towards booking intention. The purpose of this conceptual paper is to propose a study that brings out an exploratory research which intends to analyze and determine the factors that lead to active participation and engagement among consumers within social media, paying attention towards three different processes of social influence: compliance, identification, and internalization that can foster individuals’ attitude and behavioral changes. The improvement of social media marketing will enhance positive electronic word-of-mouth (eWOM) and consequently lead to intention to purchase, in addition to development of a robust, attractive image and product within online communities. Information within this study is regarded as valuable resource that could be used by online hotel marketers as well as related social media manager, as they can acknowledge and understand the actions and practices needed in social media to direct them towards business growth and positive online marketing practice.